Patient’s Awareness and Knowledge of Root Canal Treatment (RCT): A Survey-Based Original Research at RIPHAH International - Abdul Haq, Saadia Ejaz Bokhari, Muhammad Arslan Rana, Muteen Fatima, Abdul Rehman, Arfa Sabir Hussain (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: The goal of this research was to find out whether people’s perspectives about root canal therapy have shifted over time in a representative sample of the Islamabad community and, if so, in what ways. Materials and Method: At the Islamic International Dental Hospital, 103 patients underwent a cross-sectional study. The study’s goal was to find out how much participants knew about root canal therapy (RCT). Root canal therapy patients completed a self-report questionnaire, which included 18 items with multiple choice answers. Results: 103 patients were studied. Among those 77 out of 103 were females and 26 were males. Out of 103 individuals 20 people had no previous knowledge of treatment, 5 individuals were not interested and the remaining 78 had a varying degree of knowledge. Regarding the fears leading to apprehensive attitude among patients to seek treatment the most common fear was the fear of pain prevailing in 57 out of 103 individuals. Chi-square test was run to analyze association among age groups, gender identity and qualification of the respondents with all the questions from the questionnaire from the twin cities. There was a significant relationship between the knowledge and awareness among patients i.e 0.___ Conclusion: Ache in the tooth is the main cause of patients coming to dental hospitals. The awareness about dental therapy has been elevated among the people but the dentists should still inform and educate the patient about importance of dental health and dental treatments. Keywords: Awareness, Dentistry, Endodontic, Knowledge.